Study of Organizational Culture Emotional Quotient and Work Motivation on Employee Performance (Empirical Study on HR Bureau and General Supervisory Commission Business Competition) - Yusnita, Nancy; Samuel, Bryllee; Wahyuni, Elsa Eka (Share : Social Work Journal, 2025)
Employee performance plays a crucial role in determining the success of an organization or institution. Consequently, organizations make continuous efforts to enhance employee performance to ensure that their goals are achieved. One factor that contributes to performance outcomes is individual ability, which includes emotional intelligence. Therefore, elements such as organizational culture and emotional intelligence must be taken into account when seeking to improve employee performance. This study aimed to identify strategies for enhancing employee performance by examining the relationships among the research variables. The research was carried out at the Human Resources and General Bureau of the Business Competition Supervisory Commission (KPPU) to assess the influence of organizational culture and emotional intelligence on employee performance. A quantitative approach was employed, with data gathered through questionnaires distributed to employees. The study applied a saturated sampling method, meaning that all members of the population were included as respondents, resulting in 88 participants. Data were analyzed using descriptive statistics and path analysis. The findings indicated that employee performance can be improved by aligning organizational culture, fostering emotional intelligence, and strengthening employee work motivation.